Letter - Kean, William
012a-0112-001 General President: W. H. ASHFORTH. General Secretary: WM. KEAN, J.P. Affiliated to the Trades Union Congress and the Labour Party Registered July 1912 under Trades union Acts 1871 and 1876 The National Union of Gold, Silver and Allied Trades. SHREWSBURY CHAMBERS. 34 CAMPO LANE, SHEFFIELD. 1, Sir Walter Citrine K.B.E. General Secretary. Trades Union Congress. Transport House. Smith Square. LONDON. S.W.1. April 2nd 1938 Dear Sir Walter, I am quite agreeable to the Finance and General Purposes Committee interviewing Lord Halifax, on matters affecting the struggle in Spain. Yours Respectfully Wm Kean REF/WK/EC. 292/946/12a/112